Backlund Transformations for the Isospectral and Non-isospectral Matrix Kdv Hierarchies (Journal of Partial Differential Equations, 2020)
By transforming the usual Lax pairs of isospectral and non-isospectral matrix Kdv hierarchies into Lax pairs Riccati form, a unified explicit from of Backlund transformations and superposition formulas for these two kinds of hierarchies of equations can be ohtaincd.
Keywords: Backlund transformation; noncommutativity of matrix; Lax pairs